2022
DOI: 10.1021/acsami.1c19397
|View full text |Cite
|
Sign up to set email alerts
|

Facile Approach to Enhance Electrical and Thermal Performance of Conducting Polymer PEDOT:PSS Films via Hot Pressing

Abstract: This paper studies the impact of hot pressing on the electrical and thermal performance of thick (thickness >5 μm) conducting polymer poly(3,4-ethylene dioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) films after acid treatment. Thick conducting polymer films usually exhibit low electrical and thermal conductivities similar to bulk polymer because charge and heat carriers are easily scattered by the irregular arrangement of crystalline domains inside the polymer. In this work, the in-plane electrical conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…The PSS/PEDOT weight ratios are 1.61 and 1.91 for the A-PEDOT:PSS and I-PEDOT:PSS films, respectively. Compared with the original PH-1000 solution, both the as-obtained A-PEDOT:PSS and I-PEDOT:PSS films possess evidently lower PSS contents, which can be attributed to the effect of H 2 SO 4 treatment during the film preparation processes. ,,, Commonly for the I-PEDOT:PSS films, as the diffusion depth of H 2 SO 4 in the films is quite limited, their σ can hardly be enhanced. ,, However, it is noted that for the A-PEDOT:PSS films, H 2 SO 4 treatment has been effectively applied to each individual fiber prior to wet-winding. The removal of the insulating PSS segments, therefore, can be relatively more thorough.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The PSS/PEDOT weight ratios are 1.61 and 1.91 for the A-PEDOT:PSS and I-PEDOT:PSS films, respectively. Compared with the original PH-1000 solution, both the as-obtained A-PEDOT:PSS and I-PEDOT:PSS films possess evidently lower PSS contents, which can be attributed to the effect of H 2 SO 4 treatment during the film preparation processes. ,,, Commonly for the I-PEDOT:PSS films, as the diffusion depth of H 2 SO 4 in the films is quite limited, their σ can hardly be enhanced. ,, However, it is noted that for the A-PEDOT:PSS films, H 2 SO 4 treatment has been effectively applied to each individual fiber prior to wet-winding. The removal of the insulating PSS segments, therefore, can be relatively more thorough.…”
Section: Resultsmentioning
confidence: 96%
“…24,26,35,48 Commonly for the I-PEDOT:PSS films, as the diffusion depth of H 2 SO 4 in the films is quite limited, their σ can hardly be enhanced. 24,25,49 However, it is noted that for the A-PEDOT:PSS films, H 2 SO 4 treatment has been effectively applied to each individual fiber prior to wet-winding. The removal of the insulating PSS segments, therefore, can be relatively more thorough.…”
Section: Resultsmentioning
confidence: 99%
“…308 Another example exploits hot pressing to enhance the electrical and thermal performance of conducting PEDOT:PSS films. 303 The performed experiments have suggested that the hot pressing induced significant changes in molecular conformations, with respect to the crystallite size and molecular orientation, that decreased the p-p stacking distance and thus, lowered the activation energy for charge carrier hopping, finally leading to more than 50% increase in electrical conductivity. 303 An increase of the latter was earlier reported when hot pressing carbon nanotubes/ PEDOT:PSS composite films.…”
Section: -Published By the Royal Society Of Chemistrymentioning
confidence: 99%
“…As a state-of-art TE material near RT, Bi 2 Te 3 , however, cannot be employed directly for f-TEGs due to its rigidity and brittleness. Organic TE materials, such as poly­(3,4-ethylenedioxythiophene) (PEDOT) and polyaniline (PANI), are inherently flexible, but their α values are often small, which directly leads to the PF values of organic materials usually lower than 5 μW cm –1 K –2 . Moreover, the TE property optimization of organic materials is difficult, which is not conducive to the realization high output power of f-TEGs assembled with organic TE materials. Organic/inorganic composites prepared by suitable methods can achieve both high TE performance and deformability. Among them, depositing inorganic materials on flexible substrates has been demonstrated as an effective method to fabricate high-performance flexible TE materials. , For example, high-performance Bi 2 Te 3 films with controllable microstructures were deposited on flexible polyimide (PI) substrates by magnetron sputtering, and the PF could reach 2170 μW m –1 K –2 at RT .…”
Section: Introductionmentioning
confidence: 99%